Judicial independence in Nigeria: Between global trend, domestic realities and Islamic law - Sule, Ibrahim (2014)
Judicial independence has its origin in the theory of separation of powers.As for the judiciary, the theory means both the judiciary as institution and all individual judges and other personnel must be able to carry out their professional responsibilities free from any influence or interference by the Executive or Legislature or any other person or institution outside or within the judiciary. Undoubtedly, it is only an independent judiciary that can competently provide the necessary checks on the excesses of other arms of government particularly on breaches of rights and freedoms of the citizenry.This paper establishes that independence of judiciary is an indispensable ingredient of good governance. It also analyses judicial independence in Nigeria in line with some global trends and discovered ironically that even though the Nigerian Constitution guarantees one’s rights to have one’s cause heard by an independent and impartial judge, it does not guarantee institutional independence of Nigerian judiciary at all.And this could have been the reason why the fortunes of Nigerian judiciary is day by day dwindling as it is compelled by lack of constitutional guarantees to always beg either the executive or the legislature for one ‘favor’ or another.The paper also analyses some of the causes of the persistent crisis in the Nigerian judiciary and also highlights on some lessons to be learnt from judicial independence under Islamic law.